Homem e mulher à sua imagem os criou: Reflexões bíblico teológicas, hermenêuticas e eclesiológicas sobre a questão da homossexualidade - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2012)
The present article is a positioning on the theological theme of homosexuality. On a first moment, the author affirms the necessity of comprehending the Scriptures, also inside the modern and post-modern cultural coordinates, as public truth, which concerns all human beings and which possesses supra individual meaning, as well as universal validity and claim. At a second moment, the author pleads to the freedom of expression and for the respect of the human rights. Following, the author approaches the question of hermeneutical nature, affirming the necessity of guiding ethical decisions and theological positions under the authority of the Holy Scriptures. He emphasizes the necessity of rescuing today what is called the “hermeneutical trust” in the Scripture’s words. In continuity, he presents observation of exegetical character from the Old and New Testament, and reaches the results that the Holy Scriptures are favorable to the stable union between people of different gender, as well as contrary to the practice of homosexuality. At the end, the author presents a series of reflections regarding the Christians and the Christian churches’ handling of the person with homosexual tendency or practice, seeking the reception and the person’s transformation through the gospel’s light.
Keywords: Homosexuality; church and homosexuality; homosexuality in the Bible